Effect of mare's breed on the fatty acid composition of milk fat - R. Pietrzak-Fiećko; R. Tomczyński; A. Świstowska; Z. Borejszo; E. Kokoszko; K. Smoczyńska (Czech Journal of Animal Science, 2009)
Gas chromatography and IDF Standard method (1999) were used to analyze the fatty acid composition of milk fat of mares originating from the following breeds: 10 of Wielkopolska breed, 10 Konik Polski Horses, and 9 Polish Cold-blooded Horses. Eighty-seven mare's milk samples were collected in the years 2000-2002. Unsaturated fatty acids were shown to prevail in the milk fat of mares of Wielkopolska breed (61.32%) and of Konik Polski mares (52.58%) whereas saturated acids prevailed in the milk fat of Cold Blooded mares (54.95%). The study revealed that the fatty acid composition of the investigated groups of mares was breed-specific. Of course, the impact of other uncontrolled factors such as nutrition is not excluded, either.